Design of vibration sensor based on fiber Bragg grating - Zhengyi Zhang; Chuntong Liu (Photonic Sensors, 2017)
Abstract Fiber grating is a kind of new type of fiber optic light source device which has been rapidly changing in the refractive index of the core in recent years. Especially, it can realize the high precision of the external parameters by means of the special structure design and the encapsulation technology [1, 2]. In this paper, a fiber grating vibration sensor which is suitable for vibration monitoring in key areas is designed based on the technical background of vibration monitoring system. The sensor uses a single beam structure and pastes the fiber Bragg grating (FBG) to measure the vibration wavelength on the surface. When the vibration is simply harmonic vibration, the Bragg reflection wavelength will change periodically, and the periodic variation of the wavelength curve can be measured by the fiber grating demodulator, then the correctness of the experimental results is verified. In this paper, through the analysis of the data measured by the demodulator, the MATLAB software is used to verify the data, and the different frequency domains, the modes, and the phase frequency curves are obtained. The measurement range is 0 Hz–100 Hz, and the natural frequency is 90.6 Hz.